Remembering to Take Your Diabetes Medications - Linda B. Bobroff (EDIS)
FCS8930, a 1-page handout by Linda B. Bobroff, provides tips for helping people remember to take their diabetes medications on time. Published by the UF Department of Family Youth and Community Sciences, September 2010.